Some Organotellurium(IV) Complexes of 1-Methyl-3-(p-tolylimino)indolin-2-one Schiff Base - Kumar, Manish; Verma, K.K.; Garg, Sapana (Asian Journal of Chemistry, 2021)
Six new hexa-coordinated organotellurium(IV) complexes of type RTeCl3·NMeIPT and R2TeCl2·NMeIPT (R = 4-hydroxyphenyl, 4-methoxyphenyl or 3-methy-4-hydroxyphenyl; NMeIPT(L) = Schiff base (1-methyl-3-(p-tolylimino)indolin-2-one) derived from condensation of 4-methylisatin and p-toluidine) have been synthesized and characterized by different spectral studies like elemental analyses, molar conductance, infrared, mass spectrometry, 1H NMR, 13C NMR and UV-visible spectroscopy. On the basis of spectroscopic data, it is evident that Schiff base behaves as NO donor bidentate ligand via azomethine nitrogen atom and oxygen atom from carbonyl group for all the tellurium(IV) complexes. The results showed that all the organotellurium(IV) complexes possess distorted octahedral geometry. Geometry of the all organotellurium(IV) complexes was optimized and their theoretical quantum mechanical parameters were calculated. This computational study also suggests octahedral geometry for complexes. The antimicrobial activity of NMeIPT and all the organotellurium(IV) complexes were screened against bacteria i.e. Xanthomonas campestris and Bacillus cereus and fungi i.e. Fusarium oxysporum, Candida albicans and Sclerotinia sclerotium.